2019
DOI: 10.1016/j.rmcr.2019.100950
|View full text |Cite
|
Sign up to set email alerts
|

Drastically progressive lung cavity lesion caused by Actinomyces odontolyticus in a patient undergoing chemoradiotherapy: A case report and literature review

Abstract: Pulmonary actinomycosis reportedly forms 15% of all cases of actinomycosis, and pulmonary Actinomyces odontolyticus is particularly rare. A 60-year-old man with a hoarse voice was referred to our hospital. Lung squamous cell carcinoma was diagnosed at the clinical tumor-node-metastasis stage of cT2N2M0, and concurrent chemoradiotherapy was initiated. Further, a small cavity was also detected in the left upper lobe, but it was observed. During chemoradiotherapy, the small cavity lesion rapidly increased accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Twenty‐one cases of pulmonary actinomycosis caused by A . odontolyticus , 8–25 one case of empyema caused by L . rhamnosus 26 and 89 cases of empyema caused by S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐one cases of pulmonary actinomycosis caused by A . odontolyticus , 8–25 one case of empyema caused by L . rhamnosus 26 and 89 cases of empyema caused by S .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our literature review are summarized in Table 1. Twenty-one cases of pulmonary actinomycosis caused by A. odontolyticus, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] one case of empyema caused by L. rhamnosus 26 and 89 cases of empyema caused by S. mitis were identified. [27][28][29][30] Of these cases, 84 were identified as a part of a retrospective audit examining the aetiology of community-acquired lung abscesses diagnosed at one Japanese healthcare service.…”
Section: Case Reportmentioning
confidence: 99%
“…Pulmonary actinomycosis gradually spreads with air-space consolidation, adjacent pleural thickening, or cavitation in the lung fields 1,2. Oral insanitation, diabetes, and frequent alcohol consumption are risk factors for pulmonary actinomycosis,5 whereas only few cases of pulmonary actinomycosis have been reported in immunocompromised patients undergoing chemotherapy or immunosuppressive therapy 6. On the other hand, mucormycosis occasionally occurs in immunocompromised patients and is often a progressive and fatal disease 7.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Oral insanitation, diabetes, and frequent alcohol consumption are risk factors for pulmonary actinomycosis, 5 whereas only few cases of pulmonary actinomycosis have been reported in immunocompromised patients undergoing chemotherapy or immunosuppressive therapy. 6 On the other hand, mucormycosis occasionally occurs in immunocompromised patients and is often a progressive and fatal disease. 7 For patients who need HSCT, mucormycosis must be treated before HSCT is performed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to A. israelii , a review of nearly 500 clinical isolates of Actinomyces demonstrated the importance of A. meyeri, A. gravenitizii and A. odontolyticus as the primary Actinomyces sub-species isolated within the thoracic cavity to date [ 8 ]. These species have been associated with case reports of empyema, organizing pneumonia and cavitary lesions, respectively [ 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%